The Use of Turbo Media on the Mastery of Basic Movement Skills in Throwing Elementary School Students - Sofyan, Davi; Fikrianto, Ryan Satria; Fauzi, Riza Sukma (Universitas Negeri Semarang, 2021)
This study aims to analyze how much influence the turbo media has on the javelin throwing skill. The method used in this research is the experimental method. The research design used was the-one group pretest-postest desigen. In this research design, the first step taken was to do a pretest, then give treatment (treatment) and finally give a posttest or final test. Based on the significance value for the t test for experimental class 1 of 0.000 <0.05 and for the significance value of the experimental class 2 of 0.000 <0.05 the Ho test criterion is rejected meaning that there is an effect of turbo media on javelin throwing skills. For the difference value for the experimental class 1 is 73,900 and for the difference value for the experimental class 2 is 48,750. Concluded that the application of the turbo learning media has influence on the improvement of javelin throwing skills